Interfacial tuning and designer morphologies of microporous membranes based on polypropylene/natural rubber nanocomposites. Issue 41 (24th June 2021) - Bicy, Kottathodi; Rouxel, Didier; Poncot, Marc; Royaud, Isabelle; Bourson, Patrice; Chapron, David; Kalarikkal, Nandakumar; Thomas, Sabu
Abstract: Microporous polypropylene (PP) nanocomposite membranes are in great demand in various fields such as energy harvesting, water purification, and other industrial applications. Thin films of PP/natural rubber (NR) blend nanocomposite have been prepared by melt mixing and the membranes are made porous by extracting the NR phase from the blend. The present study gives a better insight into the nanoparticle shape and localization‐tailored porous morphology of PP membrane. Thermodynamic prediction of nanofiller localization and its impact on morphology were studied. 2D clay platelets in PP matrix tune the morphology of the porous membrane into lamellar, whereas spherical nanofillers give elongated spherical pores. The localization of nanoparticles was observed using transmission electron microscope, which is also confirmed from theoretical prediction of localization of nanofillers with the help of interfacial energy and surface tension. Thermal studies reveal that nanofillers enhance the thermal stability of polymers. Mechanical studies reveal that nanoparticles improve the mechanical properties of the system. 2D platelet shaped‐nanofillers enhance the mechanical strength of the polymer up to 39%, which is higher than that obtained for 3D spherical nanofillers. Nanofiller shape and localization have a great influence in deciding the properties and porosity of the membrane. Abstract :